Simultaneous glycerol dehydration and in situ hydrogenolysis over Cu-Al oxide under an inert atmosphere - Mane, Rasika B.; Rode, Chandrashekhar V. (Green Chemistry, 2012)
Among various catalysts screened, the Cu-Al oxide catalyst, prepared by a co-precipitation method, exhibited excellent activity for simultaneous glycerol dehydration and its hydrogenolysis without external hydrogen. Detailed characterization by XRD, XPS, HR-TEM, TPR, etc., showed evidence of Cu2+ in the form of CuO and CuAl2O4, along with Cu-0 and Cu1+ species, which are responsible for their multifunctional roles in glycerol APR, dehydration and hydrogenolysis reactions under inert conditions. This catalyst also presented consistent activity for a duration of 400 h for autogeneous hydrogenolysis of refined glycerol with 36% selectivity to 1,2-propanediol (1,2-PDO). Manipulating the temperature and feed flow rate conditions, meant that the selectivity to acetol and 1,2-PDO could be tailored as desired. Substantial enhancement in 1,2-PDO selectivity (75%) was achieved for an aqueous bio-glycerol feed over the same catalyst for 50 h of testing.